2018
DOI: 10.1111/crj.12911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and validation of bronchiectasis severity score systems for post‐tuberculosis bronchiectasis

Abstract: There are apparent differences on radiologic features between bronchiectasis patients with and without history of pulmonary tuberculosis. Both FACED and BSI can predict mortality in post-tuberculosis bronchiectasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…Previous studies of the BSI and FACED scores have been conducted in Europeans with bronchiectasis from different backgrounds, but these scoring systems have also been proven to be useful predictors of prognosis in Asians. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the BSI and FACED scores have been conducted in Europeans with bronchiectasis from different backgrounds, but these scoring systems have also been proven to be useful predictors of prognosis in Asians. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Non-tuberculous mycobacterial lung disease also presents higher percentages than Western countries (nearly 5%); 24 h gastroesophageal pH monitoring would benefit patients with gastroesophageal reflux-related bronchiectasis. [ 3 7 8 ] Studies have shown that rheumatoid arthritis, chronic obstructive pulmonary disease, asthma, and chronic rhinosinusitis are associated with bronchiectasis. [ 9 10 11 12 ] Thus, attention should be paid to these factors to detect bronchiectasis in its initial stages and utilize optimization of patient care in China.…”
Section: P Ay M Ore a mentioning
confidence: 99%
“…Patients with post-TB bronchiectasis typically show airflow obstruction in addition to recurrent episodes of purulent sputum production and haemoptysis [ 9 , 10 ]. Although two studies assessed the performance of bronchiectasis severity scoring systems in post-TB bronchiectasis [ 11 , 12 ], there is limited information on the clinical characteristics of post-TB bronchiectasis in the context of a bronchiectasis cohort.…”
Section: Introductionmentioning
confidence: 99%